From Textuality To Discursity; The Hermeneutics of Quran Nasr Hamid Abu Zayd - Sulaiman, Ahmad (UIN Mataram, 2023)
The agenda of Islamic renewal has declined due to the stagnation of the Al-Qur'an reading model that has occurred for thousands of years. Nasr Hamid Abu Zayd, an Egyptian intellectual, sees this happening because of the overlap between text and meaning as a consequence of the sanctification of the verses of the Qur'an as the word of God which contains absolute truth and creates the impossibility of interpretation beyond the literal meaning of the text. Responding to these conditions, Abu Zayd presents a thesis regarding the textuality of the Qur'an or that the Muslim holy book is a cultural product that contains objective meaning which must be revealed through an understanding of horizontal interactions with the socio-historical world. The implication is that the Qur'an is a textus receptus (received text/mushaf) which must be approached by borrowing various methodologies such as hermeneutics, semiotics and language. Only then, according to Abu Zayd, can the objective meaning of the text free from ideology and subjectivism be achieved. This paper will elaborate on the phenomenon of impasse in the meaning of the Qur'an along with Nasr Hamid Abu Zayd's methodological-hermeneutical proposal regarding both the textuality and the discoursiveness of the Qur'an. Next, some application of Abu Zayd's hermeneutics in usury, polygamy and hakimiyat will be elaborated.